2019
DOI: 10.3389/fphys.2019.00845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Muscle-Pump Baroreflex of Individual Leg Muscles During Standing

Abstract: Activation of leg muscles is an important component in the regulation of blood pressure during standing, failure of which could result in syncope and falls. Our previous work demonstrated baroreflex mediated activation of leg muscles (muscle-pump baroreflex) as an important factor in the regulation of blood pressure during standing; however, the effect of aging on the muscle-pump baroreflex of individual leg muscles during standing remains to be understood. Here, the interaction between systolic blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Based on the observation that both postural and BP control deficiencies are prevalent in normal aging, it is expected that the cardio-postural model could provide a more comprehensive way to describe the BP regulation mechanism in older persons. We have shown reductions in muscle-pump baroreflex in older compared to young persons 51 , which is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the observation that both postural and BP control deficiencies are prevalent in normal aging, it is expected that the cardio-postural model could provide a more comprehensive way to describe the BP regulation mechanism in older persons. We have shown reductions in muscle-pump baroreflex in older compared to young persons 51 , which is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, no such difference was found in men ( 88 ). Another study demonstrated that women may exhibit lower values of cardiac and muscle-pump baroreflexes compared with men ( 89 ), a finding that may lead to the conclusion that older women are more vulnerable to orthostatic intolerance compared with older men.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Verma et al ( 89 ) assessed the impact of aging on muscle-pump BRS of the lateral gastrocnemius, tibialis anterior, medial gastrocnemius and soleus muscles ( 89 ). Lower cardiac BRS control was observed in the older group of patients.…”
Section: Agingmentioning
confidence: 99%
“…Our analysis showed impaired baroreflex control in the patients compared to controls both during the sitting and standing phases of the recording. While baroreflex control is pivotal in maintaining short-term cardiovascular homeostasis in response to postural changes, long-duration stable standing would entail continuous pumping of the pooled venous blood back to the heart, by contracting lower leg muscles, to ascertain regulation of cardiac output failure of which may prompt lightheadedness [50]- [55]. Given leg muscle contraction is dependent on neural control [56], [57], ischemic stroke patients may find contracting leg muscles to facilitate venous return to heart demanding due to stroke-related impairment in motor circuit [58]- [60].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, sympathetic and vagal activities are observed to be coupled and exhibit alteration in coupling behavior with posture and disease [63]- [65], this coupling behavior can be exploited to gain additional insights regarding the complex physiological interplay between the two arms of the autonomic nervous system in the regulation of system homeostasis. Moreover, the effect of gender on the long-term effect of ischemic stroke was not performed in this study and should be considered in the future, given women are more vulnerable to orthostatic intolerance and poorer recovery following stroke [55], [66]- [70], further in our study, 4 out of 6 patients who did not exhibit SBP↔RR coherence greater than 0.5, were females suggesting females may have more profound residual effect of ischemic stroke, therefore, a comprehensive study of the relationship between gender and long-term effect of ischemic stroke is warranted and such understanding could have clinical implications. Finally, the analysis results showcased the limitation of current rehabilitation strategies which failed to restore the autonomic functionality following the ischemic stroke and demand further development of novel rehabilitation schemes to address unmet clinical needs.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%